STOCK OPNAME KOLEKSI PERPUSTAKAAN SEKOLAH DASAR NEGERI 34 PONTIANAK KOTA - Ilham Subagio; Antonius Totok Priyadi (Universitas Tanjungpura, 2020)
AbstractThis research discusses about stock opname collection Pontianak City. the purpose of this study was to determine the activities stock opname collections, advantages and disadvantages. This activity uses a qualitative method in the form of descriptive research. Data collection by observation, interview, documentation, the number of informants in this study were three people, namely the principal, teacher, and library staff. The results of this study indicate that the librarian. The results of this study indicate that the librarian SDN 34 Pontianak City . do this activity with the method of list / registration containing the parent number. The advantage of this research is to be able to know the condition of library materials, in order to take eradication measures for collections that are not feasible, so that the development of collections can be done, making it easier to find library materials. requires a short amount of data collection time, cannot borrow collections during the activity. Can be concluded that stock opname library collection SDN 34 Pontianak City only using the register/ registration method containing the parent number, using this one method can do the mess stock opname collection in the library SDN 34 Pontianak City. Keywords: Collection, School Library, Stock Opname